Process optimization to reduce draw stage for an automotive stamped part / Muhammad Faisal Mohd Latafi - Mohd Latafi, Muhammad Faisal (2011)
Nowadays, large variety automotive parts are produced from deformation process. Sheet metal forming is one deformation process which transforms a metal blank into a component. Wrinkling and tearing is the most prevalent material instabilities that occur in sheet metals formed by stamping and deep drawing process. Autokeen Sdn. Bhd. faced a problem with the manufacturing process of the Bracket Assembly Spring Upper which manufactured by using semi-progressive die. The objective of this project is to compare the behaviour between the actual soft tooling and hard tooling (progressive die) with the simulation using DYNAFORM software. The simulation results focused on the formability of the part, thickness and the major strain distribution for each stage of the drawing process. Finally, the outcome of the project is the recommendation to optimize the processing steps by reducing the drawing steps to get lower cost and higher production efficiency.